Apostol Arsaki: A Statesmanship Filled with Trials, and the Education of Women - D. Michalopoulos (University of Sofia, 2008)
Was he Romanian? Was he Greek? A prestigious physician? A Freud forerunner? A Balkan statesman? The main 19th century theoretical adversary of Marx and Marxism? A great reformer of educational systems? Truth to tell, Apostol Arsaki was all these: a famous oculist (the first one in the Balkans to have the relevant university degree) but a right-wing Romanian statesman, who granted large sums of money to Greece, in order to set up girls' schools working along the lines he regarded as being morally (and spiritually) the right ones. The study of his life and achievements is a daunting task; nevertheless is a righteous mission; so let us proceed.